Effectiveness of an Educational Program regarding the Knowledge of women about maternal care during the postpartum period that attending to the primary health care centers at AlAmara City / Iraq - Rasha Neamah; Ezedeen Bahaaldeen; Iqbal Abbas (Kufa Journal for Nursing Sciences)
Background: Postpartum care as one of the most important components of health care contributes to the prevention of maternal complications and improvement of maternal/neonatal health. In addition to meeting mothers’ mental and emotional needs consist of providing basic health education to mothers and her families, preparing mother to accept their maternal roles and encouraging an effective progress to motherhood.